Paradigma Dakwah Islam Fethullah Gulen di Abad Kontemporer - Akhmad Rizqon Khamami (Islamica: Jurnal Studi Keislaman, 2018)
This article seeks to examine Fethullah Gulen’s da‘wah activities by which he integrates his movement into the globalized world. Despite the fact that Turkish Coup in 2016 tarnished Gulen and his movement, and scholars come to question Gulen’s intentions, Gulen’s activities are to be explored so as for Islamic movements somewhere else to emulate his success in da‘wah. This article offers a perspective using the da‘wah approach. Question under discussion in this article is as to which steps of da‘wah lead Gulen movement to be a respected Islamic movement prior to the 2016. Gulen managed to widen the da‘wah from merely conventional da‘wah such a that of preaching into educations, dialogues, and economic. It is indeed Gulen’s emotional preaching that fascinates listeners and drives them voluntarily to engage in his activities of da‘wah and to give hand to his missionary works which include building schools, TV stations, radios, hospitals, and banks. Gulen’s da‘wah in economic goes in line with his effort to broaden his influence on international level which in turn leads the movement integrated into the global economy. It is interfaith dialogue and pluralism that bring Gulen into integrating Islam with cosmopolitanism in the globalized world. Muslims no longer belong solely to ummah, but they are citizen of the globalized world.